Revolutionizing healthcare with metamaterial-enhanced antennas: a comprehensive review and future directions - Asokan, Sakthi Preetha; Kaliappan, Kavitha (Frequenz, 2024)
The state of the art for wearable antennas for wireless communication and biological applications is compiled in this article. It addresses a wide range of subjects, such as how to use novel materials like Artificial Magnetic Conductors (AMC) and Metamaterial (MTM) structures to enhance antenna performance. It also covers the design of dual-band and reconfigurable antennas and the use of machine learning to optimize aerial design. The main subject of this article is how wearable antennas could lead to advancements in wireless communication and healthcare in the future, perhaps improving lives worldwide. It includes implantable antennas, textile-based antennas, and various flexible graphene-based antenna varieties. The use of wearable antennas for brain stroke diagnostics, wireless body area networks, telemedicine, and breast imaging is covered in this study. Additionally covered are reconfigurable antennas based on Metamaterial (MTM)structures and Wideband on-body antennas inspired by Metamaterials (MTM), both of these applications are useful in the assembly of wearable antennas, which is the main goal of this work. The research also discusses how metamaterials (MTM) might raise the sensitivity of the bioelectric field, enabling precise bioelectric signal monitoring. Metamaterial (MTM) antennas function reliably in a range of biomedical applications and can adjust to the electromagnetic properties.